Establishment and Validation of Finite Element Model for Reinforced Concrete Columns - Li, Yulin (Scientific Journal of Technology, 2025)
Reinforced concrete structures are widely used in buildings in China. However, research on the mechanical properties of reinforced concrete components remains limited due to experimental constraints and economic factors. This study establishes a mesoscale numerical model of reinforced concrete (RC) columns using Python and ABAQUS software, followed by comparative analysis with experimental results. The results indicate that the predicted load-displacement curves and ultimate bearing capacities align closely with experimental data, demonstrating high consistency between the model and real-world conditions. This work lays a foundation for further research on the mechanical behavior of RC columns.